A household waste stream analysis in a rural Mexican location - Luis Velazquez; Carlos Anaya; Omar Contreras-Aganza; Nora Munguia (The Central European Review of Economics and Management (CEREM), 2020)
Aim: This paper presents a waste stream exploratory study with the purpose of identifying opportunity gaps to reduce environmental and health risks within the household waste stream in a small rural population in Northwestern Mexico by following the waste management hierarchy. Design / Research methods: The study consisted of three phases. Firstly, a one-stage cluster sampling was conducted to characterize the household waste in this rural population. A cluster in this study was a block. There were 54 clusters, but only 40 with occupied houses. The clusters were selected by simple random sampling. During the second phase of this study, a survey was conducted to examine the waste management practices of the residents of sampled houses. Considering that 51 were the habited houses in the sampled clusters, a simple random sampling for finite populations was selected.~ Finally, a quadrat sampling method was conducted. The total area of the municipal landfill site was divided into black and white quadrats. The white color was represented by tails while the black color was represented by heads. The color of the sampled quadrats was selected after 50 flip virtual coins for true randomness. Conclusions/findings: Findings in this study indicate the willingness of the inhabitants in this rural location to participate in source reduction initiatives. Findings also showed that organic waste was the predominant material in the household waste composition. Therefore, there are opportunities to enhance composting at home or even implement a community composting program. The riskier situations revealed by this study were observed at the landfill site where air emissions and leachate occurred. Originality/value of the article: Based on the waste stream analysis, there are some opportunities to reduce the environmental and health risks in a small rural zone in Northwestern Mexico. In this regard, this study can serve as an example to analyze and compare sustainable opportunities in other rural zones around the world.
Keywords: Q51; Q53; R11; 330; Waste management; Rural Development; Landfill; Waste Stream Analysis